Constraints of small and medium enterprises owned by Chinese immigrants in Malaysia / Ruan Mengdie - Ruan , Mengdie (2018)
This research sets out to explore and discover the main barriers to small and medium enterprises owned by the Chinese immigrants and identify policy measures that the Malaysian government agencies should take to support them. For this, it investigated the following research questions. 1. What are the demographic profiles and personal traits of Chinese immigrant entrepreneurs in Malaysian SME sector? 2. What are the main constraints and challenges faced by Chinese immigrant entrepreneurs in the Malaysian SME sector? 3. What are the main contributions made by Chinese immigrant entrepreneurs to the economy in Malaysia? 4. What are the policy measures the government could take to help the immigrant Chinese entrepreneurs to overcome the constraints and challenges they are facing currently and help to grow their businesses? This study employed qualitative phenomenological research approach and case study method, and an integrated theoretical framework which included cultural theory, ethnic enclave theory, disadvantage theory and mixed embeddness theory. The study used primary data gathered from 15 Chinese immigrant business owners of diverse SMEs (older than 3 years) in Kuala Lumpur, Malaysia. For data analysis, an analytic framework has been framed from literature review which identified seven main constraints to entrepreneurial activities among Chinese immigrants in Malaysia: (a) Low human capital; (b) Low management; (c) Lack of financial supports; (d) Low social networking; (e) Lack of technology and innovation; (f) Lack of marketing; (g) Lack of government assistance. The research findings show that the demographic profiles and personal traits of Chinese immigrant entrepreneurs in Malaysian SME sector include: most of them are in the 30 to 40 age group, six business owners are in the 40-50 group, married, and hold at least bachelor‘s degree In terms of perceptions of personal characteristics of an entrepreneur, innovative is viewed as the most important personal traits for an entrepreneur, followed by sociable and decisiveness. They also show that the entrepreneurial activities of Chinese immigrants in Malaysia are indeed constrained by the seven factors identified in analytic framework, and that the Chinese immigrant entrepreneurs received little assistance from government agencies. The study found that SMEs owned by the Chinese immigrants make significant contributions to the economy in terms of creating employment, creating wealth, producing diverse goods and services and helping to increase exports. The findings are significant for informed policy making as they highlighted the main constraints faced by the Chinese immigrants owned SMEs. It is important that government comes up with specific policies to support these SMEs for growing and expanding their businesses, thereby increasing their contributions to the national economy such as job creation, wealth accumulation and diverse economic productive activities. The study makes following recommendations for future research: (i) to undertake similar study with participants from other ethnic groups such as Indian and Iranian; (ii) to conduct same study covering different regions or cities in Malaysia because of the influence of environmental factors; (iii) to conduct the same study with participants of identical gender.